Mistrust of mental health services: ethnicity, hospital admission and unfair treatment. (June 2015) - Henderson, R. C.; Williams, P.; Gabbidon, J.; Farrelly, S.; Schauman, O.; Hatch, S.; Thornicroft, G.; Bhugra, D.; Clement, S.; the MIRIAD study group
<x content-type="archive" xml:space="preserve">Abstract</x> Aims. To explore the role of psychiatric admission, diagnosis and reported unfair treatment in the relationship between ethnicity and mistrust of mental health services. Methods. The Mental Illness-Related Investigations on Discrimination (MIRIAD) study was a cross-sectional study of 202 individuals using secondary mental health services in South London. Two structural equation models were estimated, one using Admission (whether admitted to hospital for psychiatric treatment in the past 5 years) and one using involuntary admission to hospital in the past 5 years. Results. Increased mistrust was directly associated with the latent variable 'unfair treatment by mental health services and staff' and with Black or mixed ethnicity in both models. Those with a diagnosis of schizophrenia spectrum (as compared to depression and bipolar disorder) had a lower average score on the latent variable, suggesting that on average they reported less unfair treatment. We found evidence of increased reporting of unfair treatment by those who had an admission in the past 5 years, had experienced involuntary admission, and for people of Black of mixed Black and White ethnicity. Conclusions. Neither prevalence of schizophrenia spectrum nor rates of hospital admission explained the greater mistrust of mental health services found among people of Black and mixed Black and White ethnicity compared with White ethnicity. Rather, people of Black and mixed Black and white ethnicity may be more likely to experience unfair treatment, generating mistrust; furthermore, this group is more likely to express mistrust even after accounting for reporting of unfair treatment by mental health services and staff.